Способ определения аскорбата лития в лекарственной форме методом вольтамперометрии - Плотников Е. В. Евгений Владимирович; Короткова Е. И. Елена Ивановна; Воронова О. А. Олеся Александровна; Дорожко Е. В. Елена Владимировна
опубл. 20.03.14